LEUKOCYTES DIFFERENTIATION OF Pangasius hypophthalmus THAT WERE IMMERSED IN Lawsonia inermis L. - Hasugian, Sampang Hotramadi; Riauwaty, Morina; Syawal, Henni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The research was conducted in June to October 2017 in Parasites and Fish Diseases Laboratory Faculty of Fisheries and Marine Science, University of Riau. The purpose of this research was to determine total leucocyt, leukocytes differentiation, and phagocytosis index of Pangasius hypophthalmus. There were five treatments applied namely negative control (Kn) was the fishes were not infected with Aeromonas hydrophila and were not immersed with Lawsonia inermis L. solution, positive control (Kp) was the fishes were not immersed with Lawsonia inermis L. solution but were infected with Aeromonas hydrophila. The dose of Lawsonia inermis L. solution were 2000 ppm (P1), 3000 ppm (P2), 4000 ppm (P3). The fishes were immersed for five minute in once a week for five times. Based on the data, it can be uncluded that the immersion with Lawsonia inermis is able to increace the immune system of the Pangasius hypophthalmus. The best dose was at 2000 ppm wich was shown by lymphocyte 83,33%, neutrophils 8,33%, monocyte 8.33%, total leukocyte 11,27x104 cell/mm3, fagocyte index 63,33%, the average of weight 6,97 g and survival rate 93,33%. Keyword: Leukocytes, Pangasius hypophthalmus, Lawsonia inermis L, phagocytosis, Aeromonas hydrophila